THE ROLE OF CUSTOMARY LAW IN THE DEVELOPMENT OF NATIONAL LAW - Mohammad Miftah (SEAN Institute, 2023)
Customary law is part of the law that is not written, lives and grows in the soul of the people and applies from generation to generation from ancient ancestors to the present day. The source of customary law is the people's belief in belief, which is expressed, among other things, in the form of customs, decisions of the heads of the people. This study aims to determine the extent of the role of customary law in the association of national law and how the function of customary law in the current era of globalization, the results of the study explain that, the existence of customary law and its position in the national legal system cannot be denied even though customary law is not written and based on the principle of legality is an illegitimate law. Customary law will always exist and live in society. Customary law is a law that really lives in the awareness of the conscience of the community which is reflected in the patterns of their actions in accordance with their customs and socio-cultural patterns which are not contrary to national interests. In the development of national law, the role of customary law is very important, this is because the national law to be formed is based on applicable customary law, but in its course customary law is unwritten and dynamic in nature which can always adapt to the development of human civilization itself.